The Effect of Temperature, Sulfonation, and PEG Addition on Physicochemical Characteristics of PVDF Membranes and Its Application on Hemodialysis Membrane - Retno Ariadi Lusiana; Ayub Indra; Nor Basid Adiwibawa Prasetya; Nurwarrohman Andre Sasongko; Parsaoran Siahaan; Choiril Azmiyawati; Nanik Wijayanti; Anugrah Ricky Wijaya; Mohd Hafiz Dzarfan Othman (Universitas Gadjah Mada, 2021)
Polyvinylidene fluoride (PVDF) membrane and its derivative have been investigated the permeation ability for creatinine and urea. The membrane was made by an inversion precipitation system in N,N-dimethyl acetamide (DMAc) and water as non-solvents. In this study, the modification of PVDF membrane permeability with PEG additives, CBT variations, and sulfonation was successfully carried out. The membrane solidification process was carried out on three variations of the coagulation bath temperature (CBT): 30, 45, and 60 °C. Eight types of membranes were characterized by using FT-IR and TGA/DSC, followed by the analysis of their porosity, hydrophilicity, water uptake, swelling degree, tensile strength, and permeability of creatinine and urea. The FT-IR spectra indicate that PVDF modification has been successfully carried out. The porosity, hydrophilicity, water uptake, and swelling degree values increase with the modification of functional groups. Furthermore, improvements in creatinine and urea permeability and clearances are achieved by increasing CBT and sulfonation in the PVDF/PEG membrane. The presence of sulfonate groups improves the membrane permeability through the interaction of intermolecular hydrogen with water and dialysate compounds. The existence of PEG as a porogen enhanced membrane porosity. Creatinine and urea clearance values increase from 0.29–0.58 and 6.38–20.63 mg/dL, respectively.